Pengembangan Video Pembelajaran Pada Materi Allah Penyelamatku Kelas V Sekolah Dasar - Ailena Manalu; Lustani Samosir; Damayanti Nababan; Nisma Simorangkir; Raikhapor Raikhapor (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The research aims to develop audio visual media on the material Allah is My Savior in Christian Religious Education learning for class V elementary school with the 2013 curriculum. This research is research and development (research and development) of audio visual media which aims to produce products and test product activity. The place of research was carried out at a State Elementary School in Simanindo District, Samosir Regency.